The Context of Suffering: Empirical Insights into the Problem of Evil - Church, Ian M. (TheoLogica, 2022)
While the evidential problem of evil has been enormously influential within the contemporary philosophical literature—William Rowe’s 1979 formulation in "The Problem of Evil and Some Varieties of Atheism" being the most seminal—no academic research has explored what cognitive mechanisms might underwrite the appearance of pointlessness in target examples of suffering. In this exploratory paper, we show that the perception of pointlessness in the target examples of suffering that underwrite Rowe’s seminal formulation of the problem of evil is contingent on the absence of broader context. In other words, we show that when such suffering is presented alongside broader contextual information, the appearance of pointlessness, on average, significantly diminishes. In §1 we briefly elucidate Rowe’s formulation of the problem of evil and the thought experiment that motivates a key premise. In §2 and §3 respectively, we briefly explain our hypothesis regarding Rowe’s case and our methods for testing these hypotheses. In §4, we elucidate our results, and in §5 we explore some of the philosophical implications of our findings and gesture towards some areas for future research. Finally, in §6, we briefly connect our research to some of the established philosophical literature on suffering and narrative before concluding.